Pengembangan Modul Akhlak-Tasawuf Berbasis Problem Based Learning di Kelas XI Madrasah Aliyah - Fuji Pratami (Edu Global : Jurnal Pendidikan Islam, 2022)
The purpose of this research and development is to describe the learning process before and after using the problem-based learning Akhlak-Sufism module, the validity and practicality of the problem-based learning Akhlak-Sufism module in Class XI Religion of MAN 1 Mandailing Natal. This research is an R&D research using the ADDIE model (Analysis-Design-Develop-Implementation-Evaluation) to produce a Problem-Based Learning Morals-Sufism Module. The test subjects in this study were Religious Akhlak-Sufism teachers of Class XI MAN 1 Mandailing Natal. The research subjects were students of Class XI Religion at MAN 1 Mandailing Natal. There are 2 types of data in this development research, namely: qualitative data and quantitative data. Data collection techniques are: 1. Needs analysis instruments, 2. Validity instruments, and 3. Practicality instruments. The results of the validation of the RPP for the Morals-Sufism Subject were 90% in the very valid category. The validation results of the Problem Based Learning Akhlak-Sufism Module with a percentage of 90% are very valid categories. The results of practicality or limited trials of the Problem Based Learning Akhlak-Sufism Module with a total percentage result of 94% in the very practical category.